Grasp55 −/− mice display impaired fat absorption and resistance to high-fat diet-induced obesity - Jiyoon Kim (Nature Portfolio, 2020)
The physiological roles of the Golgi reassembly-stacking protein 55 (GRASP55/GORASP55) remain largely elusive. Here, the authors show that the Golgi-resident protein GRASP55 plays a crucial role in lipid homeostasis by regulating intestinal lipid uptake.